Die Familie Mendelssohn 1729-1847 - Hensel, Sebastian 1830-1898 (Berlin Behr, 1879)
Sebastian Hensel, a great-grandson of the philosopher Moses Mendelssohn and son of Fanny Mendelssohn, wrote this family chronicle in 1879. The Mendelssohn family is a German-Jewish family of scholars, bankers and artists. For many years, the descendants remained connected through the joint management of the Mendelssohn banking house. Numerous artists also descended from the family - among them the famous composer, pianist and organist Felix Mendelssohn Bartholdy.
See 08B24 and 08B25 for the first part in second edition and the second part in third edition
Family tree inserted at the end of vol. 3
Keywords: Mendelssohn family; Jews; 18th Century (1701-1800); 19th Century (1801-1900); Composer; Biography; Music history; Correspondence; Diary; Germany